Six species of Grandidierella collected from the Ryukyu Archipelago in Japan, with descriptions of four new species (Crustacea: Amphipoda: Aoridae) - Ariyama, Hiroyuki (Zootaxa, 2020)
Six species of the amphipod genus Grandidierella Coutière, 1904 were collected from coastal areas of the Ryukyu Archipelago in Japan. Four species are new to science and the other two are new to Japan. Grandidierella contigua sp. nov. has a characteristic male gnathopod 1 with three teeth on the carpus, the proximal tooth of which is very small and contiguous with the large middle tooth. Grandidierella gilesi Chilton, 1921 is characterized by the densely setose gnathopods and the divergent merus of the gnathopod 2 in both sexes. Grandidierella halophila Wongkamhaeng, Pholpunthin & Azman, 2012 possesses a long posteromedial projection on the male coxa 2. Grandidierella japonicoides sp. nov. closely resembles G. japonica Stephensen, 1938 in having stridulating ridges on the male gnathopod 1 carpus, but the former can be distinguished from the latter in the presence of a posteromedial projection on the male coxa 2 and the shapes of the gnathopod 1 carpus in both sexes. Grandidierella nana sp. nov. is a small species and has a wide and short carpus in the male gnathopod 1. Grandidierella pseudosakaensis sp. nov. is similar to G. osakaensis Ariyama, 1996; however, the former is different from the latter in the absence of a posterodistal projection on the male gnathopod 1 ischium and the growth process of the male gnathopods. A key to Grandidierella species in the Ryukyu Archipelago is provided.